Spectral Sufficient Conditions on Pancyclic Graphs - Guidong Yu; Tao Yu; Xiangwei Xia; Huan Xu (Complexity)
A pancyclic graph of order n is a graph with cycles of all possible lengths from 3 to n. In fact, it is NP-complete that deciding whether a graph is pancyclic. Because the spectrum of graphs is convenient to be calculated, in this study, we try to use the spectral theory of graphs to study this problem and give some sufficient conditions for a graph to be pancyclic in terms of the spectral radius and the signless Laplacian spectral radius of the graph.